Visualization and Documentation of Capsule and Melanin Production in Cryptococcus neoformans. Issue 1 (20th January 2021) - Nichols, Connie B.
Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen primarily targeting immunosuppressed populations in both resource‐rich and resource‐limited nations. Successful treatment is limited to a few antifungals that have become compromised by cryptococcal resistance, leading to intensive research seeking new drug candidates. Two distinguishing hallmarks of this species are the ability to develop a polysaccharide capsule and melanization of the fungal cells. These also act as virulence factors, protecting this pathogen in the host as well as in the environment. Here we describe two classic methods to document capsule and melanin. Although initially described and documented several decades ago, these methods remain relevant in spite of the advent of more sophisticated methodology, due in part to their simplicity and cost efficiency. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Capsule visualization by India ink counterstaining Basic Protocol 2 : Assessment of melanin on solid media Alternative Protocol : Quantification of melanin production in liquid medium